The Sr–He–Ar isotopic and elemental evidence constraints on the ore genesis of the Zhaxikang Sb–Pb–Zn–Ag deposit in southern Tibet. (6th June 2019) - Wang, Da; Zheng, Youye; Zhang, Jianfang; Wu, Song; Zhang, Sukun; Yu, Miao; Qu, Feifei
Abstract : The genesis of Zhaxikang deposit is still debated, and three main geological environments have been proposed to model the mineralization: hot spring, magmatic hydrothermal fluid, and sedimentary exhalative (SEDEX) overprinted by hydrothermal fluid. This study presents elemental and Sr–He–Ar isotopic data of minerals from different mineralization stages to support the genetic model of earlier submarine hydrothermal sedimentation (metasomatism) metallogenesis superimposed by a later magmatic‐hydrothermal fluid. The linear relations between 1/Sr and 87 Sr/ 86 Sr ratios, Sr isotopic two‐component mixing model and elemental characteristics for Mn–Fe carbonate ( 87 Sr/ 86 Sr ratios: 0.713135–0.720277, Sr concentrations: 0.72–6.05 ppm) and calcite ( 87 Sr/ 86 Sr ratios: 0.707953–0.716116, Sr concentrations: 177–1, 194 ppm) imply that the first episode of mineralization relates to a seafloor hydrothermal fluid and the second episode of mineralization is associated with a magmatic hydrothermal fluid. Furthermore, noticeable different He–Ar isotopic characteristics of the two episodes of mineralization (the first episode: 40 Ar/ 4 He: 0.06–0.27, 40 Ar/ 36 Ar: 288.9–1483.4, 38 Ar/ 36 Ar: 0.16–0.22, 3 He/ 4 He: 0.04–0.08Ra ; the second episode: 40 Ar/ 4 He: 0.23–211.76, 40 Ar/ 36 Ar: 831.5–10047, 38 Ar/ 36 Ar: 0.17–0.25, 3 He/ 4 He: 0.04–1.31Ra ) indicate that both these two episodes of ore‐forming fluids are mainly crustal‐derived with a more possibly magmatic hydrothermal origin for the second episode. Overall, the elemental and Sr–He–Ar isotopic data demonstrate the existence of two episodes of mineralization in which the initial submarine hydrothermal sedimentation (metasomatism) metallogenesis was overprinted by a later magmatic hydrothermal fluid.